On the Importance of Experience-Based Work Action and Tacit Knowledge for Workplace and Social Innovation - Neumer, Judith; Pfeiffer, Sabine (Warsaw Forum of Economic Sociology, 2015)
Companies are increasingly facing uncertainties and a variety of dimensions of imponderability. Being innovative and economically successful in turbulent times moreover increasingly requires companies to address topics of sustainability and to respect requirements of customers and other stakeholders. Companies have to bring civil society back in to find solutions to current and future challenges. But this deeply challenges the traditional forms of organisation. After an era of re-engineering organisations towards standardised processes that where tightly bound to the logic of short-term profit and shareholder markets, companies have to open up and become agile and competent for dialogue on an organisational level. This development is accompanied by the necessity to cope with uncertainties instead of annihilating them. This article argues why the tacit and experiential knowledge of employees is the key factor to tackle uncertainties and to design appropriate workplace and organisational innovation. We will outline how these factors elude approaches to formalise or digitise them and are therefore endangered by objectification of work. A new quality of participation is needed to acknowledge and support the employees' tacit and experiential knowledge and experience-based work action to strengthen processes and results of workplace innovation and social innovation.